Small scale temporal patterns of recruitment and hatching of Atlantic horse mackerel (L.) at a nearshore reef area - Klein, Maria (2018)
Atlantic horse mackerel (Trachurus trachurus, Linnaeus, 1758) is a highly exploited species, common throughout the North-East Atlantic. As a pelagic-neritic fish it typically occurs over the shelf from the surface to 200 m deep on sandy bottoms. Most research has focused on distributions of adults or early life stages (eggs and larvae) of this species in offshore waters and only a few studies have reported the occurrence of early stages near the coast. However, these nearshore environments might be important for the early growth and survival of the Atlantic horse mackerel. In addition, little is known on how environmental processes might affect the early stages of this species. Here, we monitored weekly recruitment of horse mackerel to artificial substrates (SMURFS) deployed near the coast at both the surface and near the bottom, and back-calculated hatching cohorts. The relationship of both recruitment and hatching patterns with environmental factors was investigated. From a total of 2,515 fish, 2,490 (99%) recruited to surface SMURFS. A GAM and GAMM analysis of the recruitment and hatching patterns, respectively, revealed a strong relationship with the lunar cycle and upwelling. Both recruitment and hatching showed lunar periodicity, with peaks near the new moon and revealed to be influenced negatively by upwelling. This study suggests that the nearshore environment might be an important nursery area for post-larval and early juvenile Atlantic horse mackerel